ANALISIS PENERAPAN PENDIDIKAN INKLUSI BERBASIS KURIKULUM MERDEKA DI TINGKAT SEKOLAH DASAR - Dewi Masyitoh; Deni Adi Putra; Kunti Dian Ayu Afiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze inclusive education on the basis of an independent curriculum at the elementary school level at SD Muhammadiyah 19 Surabaya. This type of research uses descriptive qualitative methods with triangulation technique data collection. Interviews given to class IV teachers and instruments distributed to observers  to observe the activities of class IV students at SD Muhammadiyah 19 Surabaya. Freedom to learn as an idea of the Minister of Education and Culture is an effort to increase educational progress. Based on the results of the interview, SD Muhammadiyah 19 fully supports learning in inclusive education based on the independent curriculum. However, the need for the help of a shadow teacher to accompany the learning process was well received. So, children with special needs can socialize with their peers and can also learn.